Nonformal Agricultural Education Reform in Uganda: The Impact on Extension Workers - Esbern Friis-Hansen; Edward Taylor; Deborah Duveskog (Adult Education Research Conference, 2014)
The purpose of this study was to explore the impact of agricultural extension nonformal education reforms (1998-2013) in Uganda among extension workers, who were required them to change from a top-down to more participatory educational approach with farmers.